Análise da competitividade da produção agrícola e do processamento da cadeia agroindustrial de suco de laranja concentrado congelado no estado do Paraná - Sabes, Jair Júnior Sanches (2012)
Brazil is the largest producer and exporter of the world market of frozen concentrated orange juice (FCOJ), and the State of São Paulo stands out as the largest producer and exporter of that commodity in Brazil. In recent years, the State of Paraná has increased its production and export of FCOJ. Through the survey of secondary data and interviews with key players, this study identified and evaluated the main critical aspects of the competitiveness of the agri-food chain of FCOJ in Paraná. Through the rapid appraisal method (method of quick research) were possible to evaluate 11 drivers of competitiveness, focusing on the links of agricultural production and processing of that chain. A total of 24 interviews were conducted, using questionnaires and interviews screenplays. It was possible to identify which are the drivers of competitiveness, considered in the context of this research, which are considered favorable, neutral and unfavorable for the competitiveness of the links of agricultural production and processing of the agri-food chain of FCOJ in Paraná. From these analyses it was also possible to verify that none of the drivers of competitiveness, considered in this dissertation, was regarded as very favorable or very unfavorable for the competitiveness of the link of agricultural production of that chain. From these analyses it was also possible to verify that none of the drivers of competitiveness, considered in this dissertation, was regarded as very favorable for the competitiveness of the link of processing of that chain, and only a driver of competitiveness, of the set of drivers considered in this dissertation, was regarded as very unfavorable for the competitiveness of the link of processing. The analyses allowed to point out proposals for public policies and private strategies to enhance the competitiveness. In a general context, it was possible to conclude that the links of agricultural production and processing of the agri-food chain of FCOJ in Paraná have a great potential to continue to expand in Paraná. The citriculture in Paraná has a great potential to expand because it has a good technology, a good production capacity and productivity and a sufficient amount of available agricultural land to extend the exploration of the citriculture in Paraná, in addition, the economic agents that act in the citriculture in Paraná have contracts for the supply of orange to the economic organizations that have manufacturing plants that produce FCOJ in Paraná, so these contracts ensure the sale of the most part of the Paraná s orange production, which is good for the citrus growers who act in Paraná. The processor sector of orange also has a great potential to expand in Paraná because it has agro-industrial technologies of good level and a good production capacity, in addition to be able to expand without great difficulties its manufacturing capacity of FCOJ, moreover, the existence of contracts for orange supply between economic organizations who act in processing and citrus growers in Paraná, secures the supply of oranges, considered of good quality, for the producing plants of FCOJ installed in Paraná.